Overview of academic research about bachelardian thought in mathematics and science brazilian teaching - Koeppe, Cleise Helen Botelho (2020)
This article composing a doctoral research by one of these authors’ developing and intend to identify the philosopher Gaston Bachelard’s ideas present in educational Theses and Dissertations published in Brazil between the years 2014 and 2018. It seeks to identify how the researchers understanding Bachelard’s theories in these works, in addition to checking the relevance of these ideas for Teaching in Mathematics and Science. The paper identifies the federative units in which these studies were developed, who are the searchs subjects and the teaching areas to which they refer. It also investigates how these ideas are employed by research in these areas of teaching. The analysis corpus consisted of 16 Theses and 49 Dissertations retrieved from the CAPES catalog of Theses and Dissertations, considering like a filters - Teaching in Mathematics and Science and Epistemological Obstacles, analyzed according to the principles of Bibliometry (HAYASHI et al. , 2008) and Discursive Textual Analysis (MORAES; GALIAZZI, 2007), characterizing the mixed methodological approach, that is, quali-quantitative. The investigated Theses and Dissertations were developed in the national territory, including teachers and students from different areas and levels of education. From the analysis of these texts, the emerging categories is The philosophical aspects in Bachelard's thought and The pedagogical aspects in Bachelard's thought, with emphasis on the thematic epistemological obstacles, error, applied rationalism, epistemological profile, general philosophy / epistemology and approximate knowledge. It was found that the Bachelard's ideas keep current and applicable to the scientific teaching-learning process, as well as corroborating and improving presently learning theories, reasons why the importance of deepening studies on the ideas of this philosopher in the brazilian courses teachers training.